Aural comprehension and oral production of young EFL learners - Lopriore, L. (Array, 2011)
This paper looks into aural comprehension and oral production of a sample of over 90 young EFL learners from Croatia and Italy. The aim was to investigate what can realistically be achieved in terms of foreign language learning (FLL) in state schools where relatively limited amounts of class time are available for foreign languages.